Sanctions for Criminal Act of Fishing with Explosives: Islamic Law Perspective - Nur Khovidatur Rohma; Rumawi Rumawi (Rechtenstudent, 2022)
The state loss of 30 trillion rupiah is part of the negative impact of the crime of fishing with explosives in Indonesia. A more severe negative impact is damage to marine habitats and ecosystems. This includes fishing with explosives accompanied by destruction to the environment. If this natural damage is not repaired immediately, then the threat of greater losses will haunt the Indonesian state which will also have a major impact on the earth's environment and global climate change. Islamic law does not tolerate any crime that harms the nation and society, which is very suitable to be a source of Indonesian law. So that the crime of fishing with explosives can be studied using Islamic law in its entirety. Then, the Qiyas method is used to analogize it to Islamic law which textually does not mention the term criminal act of fishing with explosives. Finally, the authors come to the conclusion that the crime of fishing with explosives is included in the ta'zir crime, namely a crime that does not fulfill the head or qi?as diy?t requirements perfectly. However, with this ta'zir punishment, the strict attitude of Islamic law towards the perpetrators does not disappear, in fact, these strict sanctions can be in the form of death penalty, imprisonment, exile, and fines. The party authorized to impose the sentence is Ulil-Amri, who of course must be supported by all of society, so that the sanctions imposed can be effective. Hopefully the strictness of Islamic law can become a source of positive Indonesian law in the future.